Music from the House of Hammer: Music in the Hammer Horror Films, 1950-1980 - Larson, Randall D. (Rowman & Littlefield Publishers, 1996)
In the 1950s, Hammer Film Productions, a small British filmmaking company, introduced the world to a new genre of motion picture. Referred to by some as "horror," by others as "fantasy," Hammer films had a unique look and feel that many other studios would later attempt—and fail—to capture. Hammer films also had a unique sound. For although the studio was small and the budgets limited, those involved in making the Hammer films recognized that the musical score was just as important as the set, the actors, and the script in telling the story. Consequently, Hammer Films Productions recruited the best musical talent to make its films come alive. Those artists and the work they did are chronicled here in careful detail by Randall D. Larson. From the studio's fledging days, through its great successes of the 60s and early 70s, Music from the House of Hammer offers an inside look at how the "Hammer sound" was developed and nurtured.